Policy Implementation of the Merdeka Curriculum Foundation Phase: Enhancing Collaboration and Independence among Children Aged 5–6 Years - Erna Widiastuti; Tri Rijanto; Muji Sri Prastiwi (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study investigated the implementation of the Merdeka Curriculum Foundation Phase and its contribution to enhancing collaboration and independence among children aged 5–6 years at TK Tadika Puri, South Jakarta, Indonesia. Employing a qualitative case study design, data were collected through semi-structured interviews with school principals, teachers, curriculum coordinators, and parents, complemented by classroom observations and document analysis. Participants were selected through purposive sampling based on their direct involvement in Foundation Phase curriculum enactment. Data were analysed using reflexive thematic analysis following Braun and Clarke's six-step procedure, with trustworthiness established through triangulation, member checking, peer debriefing, and thick description. Four major themes emerged from the analysis: policy communication and stakeholder understanding, classroom practices supporting collaboration, development of children's independence, and challenges and supporting factors in policy implementation. Findings revealed that effective policy communication, facilitated through iterative professional dialogue and principal leadership, progressively deepened teachers' conceptual understanding of Foundation Phase principles. Collaborative classroom practices—including cooperative play, joint problem-solving, and shared group responsibilities—produced observable improvements in children's peer interaction and cooperative behaviours. Children's independence developed along a scaffolded pedagogical pathway from teacher-directed support toward increasingly autonomous self-directed engagement, though individual developmental variability was consistently noted. Persistent implementation challenges included administrative documentation burden, variation in teacher readiness, and limited access to sustained professional development. The study contributes to educational policy implementation literature by demonstrating an empirical pathway linking policy communication processes, through classroom pedagogical practices, to observable child developmental outcomes, thereby positioning child competency development as a meaningful indicator of policy implementation effectiveness.